Using Realia to Teach Physically Disabled Students in Writing Descriptive Texts - Noorma Fitriana M. Zain (Register Journal, 2014)
This case study is focused on teaching descriptive texts by using realia. The writer took the 8th grade students of SMPLB Negeri Ungaran as the subjects of the study. The aim of this research is to know the implementation of teaching descriptive texts that cover parts, qualities, and characteristics of the objects. This study was carried out around four meetings. In each meeting, the researcher observed the situation of the class and the setudents’ activities in that classroom. The data collection method used in the research was observation, interview, and documentation. In implementating the research, the researcher found several problems and difficulties in teaching learning processes. One of them is that, the teaching physically disabled students are not easy. It has to be slowly because the students’ ability in writing the lesson is limited. The other problem comes from the teacher him/herself that never uses media or tools to teach physically disabled students. It is a matter of fact that teaching physically  disabled students needs media to make them easily understand the learning materials. One of the media that could be used is realia. From this research it is expected that the problems could be solved and a new paradigm in teaching descriptive texts for disabled students could be considered.Keywords : Descriptive Texts; Physically Disabled Students; Realia